Smoking status of pregnant women in Elazig, an eastern province of Turkey - Aksakal, Berrak Yildirim; Pirincci, Edibe; Akkus, Ibrahim Halil (Ondokuz Mayis Universitesi, 2017)
This study was conducted to determine the smoking situation of pregnant women in Elazig. Pregnant women registered at 173 family medicine centers in all the districts of Elazig comprise this descriptive research. 12.3% (n=77) of pregnant women had smoked regularly before pregnancy, 84.6% (n=531) of them stated that they never smoked and, 3.2%(n=20) had quit smoking before pregnancy. 87.7% (n=551) of pregnant women stated that they did not smoke at all during pregnancy, 4.2% (n=26) continued smoking during pregnancy, 6.7% (n=42) quit smoking as soon as they learned of their pregnancy, and 1.4% (n=9) smoking for a while and then quit smoking during pregnancy. 72.5% (n=37) of pregnant women who quit smoking, did so by themselves without any advice, 21.6% (n=11) by nurse advice and 5.9% (n=3) by doctor advice. 35.0% of pregnant women stated that they were exposed to second-hand smoking during pregnancy. The rate of smoking during pregnancy increased with decreasing income (p<0.05). The rate of smoking in pregnant women is low. The rate of pregnant women taking advice from health personnel about smoking cessation is low. The risk of smoking during pregnancy should be dwelt on by health personnel and relevant education should be given to pregnant women. © 2017 OMU.
Keywords: Pregnant; Smoking; Smoking cessation; Women